Hubungan Kadar Kolesterol Total dengan Tekanan Darah pada Pasien Hipertensi di Rumah Sakit Tingkat III 04.06.01 Wijaya Kusuma Purwokerto - Cici Farhana Ambarwanty Mohtar; Oksita Asri Widyayanti; Martha Intan Nagari Pratiwi (Jurnal Nurse, 2022)
Hypertension is still a problem in Indonesia and in other countries. Risk factors that cause hypertension pain rates are high total cholesterol levels. High cholesterol levels are experienced by many people with hypertension, will result in the formation of plaque that appears on the surface of the artery wall and has an impact on shrinking the diameter of blood vessels. The occurrence of blockages in blood vessels, which results in blood vessels having lumen (holes) then blood vessels will narrow and the elasticity of blood vessels can be reduced, this can cause hypertension. The purpose of this study was to determine the relationship between total cholesterol levels and the degree of hypertension in patients at Level III Hospital 04.06.01 Wijaya Kusuma Purwokerto. The results showed that the degree of hypertension of patients at Level III Hospital 04.06.01 Wijaya Kusuma Purwokerto there were patients with grade II hypertension as much as 54.1%, patients with grade I hypertension as much as 45.9%. Cholesterol levels with a high risk in patients as much as 54.1%, moderate cholesterol levels as much as 45.9%. The p value on the chi-square test is 0.022 (p<0.05), Fhit > Ftable means that there is a significant relationship between cholesterol levels and the degree of hypertension